Molecular phylogeny supports a new circumscription of Mimosa subser. Polycephalae, a species-rich lineage centered in the Brazilian Cerrado - Mendes, Thainara Policarpo [UNESP]; Simon, Marcelo Fragomeni; da Silva, Marcos José (Springer Nature, 2025)
With a Pantropical distribution, Mimosa is one of the most diverse genera of Tribe Mimoseae, with about 615 species. It circumscribes five sections (M. sect. Batocaulon DC., M. sect. Calothamnos Barneby, M. sect. Habbasia DC., M. sect. Mimadenia Barneby, M. sect. Mimosa), 41 series and 37 subseries, being M. subser. Polycephalae (Benth.) Barneby, the largest of them with 34 species distributed in Central Brazil. Although the species in this subseries are recognized by leaves with a pair of multifoliolate pinnae, unarmed branches, paleaceous calyx with fimbriated lobes and monadelphous filaments at the base, previous phylogenetic study recovered it as non-monophyletic with their taxa mixed with representatives of subseries Discobolae Barneby, Dicerastae Barneby, Hirsutae (Benth.) Barneby and series Modestae (Benth.) Barneby. We performed a phylogenetic reconstruction of Mimosa subser. Polycephalae and closely related taxa aiming to recircumscribe it to a monophyletic taxon and understand the relationship among its species. We sampled 30 species of M. subser. Polycephalae plus 22 from immediately related groups and performed isolated and combined analyzes of ITS (nrDNA) and trnD-trnT (cpDNA) markers using Maximum Likelihood and Bayesian Inference methods. Our analyzes confirm the non-monophyly of Mimosa subser. Polycephalae, with its taxa mixed with members of other infrageneric taxa. To make Mimosa subser. Polycephalae monophyletic, we excluded M. brevicalyx and M. cyclophylla from its concept and recognized a clade here called the Polycephalae clade, which includes taxa from subseries Discobolae, Dicerastae and Hirsutae, and ser. Modestae. Mimosa subser. Polycephalae now comprises 40 species distributed mainly in the Brazilian Cerrado, characterized by leaves lacking interpinnal spicules and predominantly with 1 pair of pinnae, which may vary between 2–4 pairs, glomerule solitary or in synflorescences, calyx vestigial or paleaceous with fimbriated lobes, and free or strongly monadelphous filaments at the base.
Keywords: Diversification; Fabaceae; Molecular phylogeny; Morphology